IMAGE PROCESSING DEVICE, IMAGE PROCESSING METHOD, AND PROGRAM - IWASA, Akio (2022)
An image processing device includes a first image processing part, and the first image processing part includes a first pixel group setting part configured to set a plurality of first pixel groups which is set to correspond to the first pixel, and which is disposed along in a plurality of directions that form a plurality of angles different from each other with respect to a predetermined direction in the first image or which is disposed along in a predetermined direction in each of the plurality of images obtained by moving the first image by a plurality of angles different from each other with respect to the predetermined direction, a first calculation part configured to calculate a plurality of first candidate pixel values on the basis of a size of the pixel value of the pixel included in each of the plurality of first pixel groups, and a first pixel value setting part configured to set the pixel value of the second pixel of the second image on the basis of the plurality of first candidate pixel values.